Ustavnosodna presoja delovnopravnih institutov - Klampfer, Marta (Delavci in delodajalci, 2012)
In most cases, the Constitutional Court is faced with the issue of labour and social relationships when reviewing constitutional complaints against the decisions of the Labour and Social Court. In such disputes, most complainants claimed violations of constitutional rights of procedural nature. The issues discussed refer to the constitutional procedural guarantee under Articles 22, 24 and 25 of the Constitution and depending on the content of the respective dispute also Articles 33, 49, 66 and 50. Constitutional Court has also been engaged with abstract assessment of the regulations concerning individual issues regarding labour law and social institutes, either on request or by an initiative filed to the Court. This paper presents some Constitutional Court reviews of labour law institutes.
Keywords: delovni spor; kršenje; procesno pravo; socialni spor; sodni postopek; ustavna pritožba; ustavna sodišča